The Contribution of Openness to Experience in Establishing Pro-Environmental Behavior - Yudi Ariana; Pratista Arya Satwika (Psikostudia : Jurnal Psikologi, 2022)
The impact of harmful human behavior on the environment is an important issue. Therefore, it is essential to discuss how humans behave towards their environment. This research objective was to examine the relationship between openness to experience and pro-environmental behavior in students and to see the description of pro-environmental behavior in students. Furthermore, the research subjects comprised 216 undergraduate students, including 58 males (26.85%) and 158 females (73.15%) with an age range of 17 to 24 years old at a university. This research used a convenience sampling technique, and the data collection tools were scales. Besides, this research used two scales: the pro-environment scale and the openness to experience personality scale. The data analysis in this research used Kendall's Tau, resulting in a correlation between openness to experience and pro-environmental behavior in students (p<0.01). It meant that the higher the level of undergraduate students' openness to experience, the higher the pro-environmental behavior they had. In addition, it was also found that the frequency distribution of pro-environment behavior data was mainly in the moderate (88.9%) categorization.Dampak dari perilaku manusia yang merugikan terhadap lingkungan merupakan isu yang penting sehingga penting untuk membahas bagaimana perilaku manusia terhadap lingkungannya. Penelitian ini bertujuan untuk menguji keterkaitan hubungan openness to experience dengan perilaku pro lingkungan pada mahasiswa dan melihat gambaran perilaku pro lingkungan pada mahasiswa. Sebanyak 216 mahasiswa yang terdiri dari 58 laki laki (26,85%) dan 158 perempuan (73,15%) dengan rentang usia 17 sampai 24 Tahun di sebuah universitas menjadi subjek penelitian ini. Teknik pengambilan sampel menggunakan convenience sampling dan skala sebagai alat pengumpul data. Terdapat dua skala yang digunakan dalam penelitian ini yaitu skala pro lingkungan dan skala kepribadian openness to experience. Analisis data yang digunakan dalam penelitian ini menggunakan kendall’s tau dan memberikan hasil bahwa terdapat korelasi antara openness to experience dan perilaku pro lingkungan pada mahasiswa (p<0,01). Artinya semakin tinggi tingkat openness to experience mahasiswa maka semakin tinggi perilaku pro lingkungan yang dimilikinya. Selain itu, juga ditemukan bahwa sebaran frekuensi data perilaku pro lingkungan mayoritas subjek berada pada kategorisasi sedang (88,9%).